The secret of natural readers : how preschool children learn to read - Anbar, Ada, 1935- (Praeger, 2004)
"Utilizing the actual experiences of six preschool children, The Secret of Natural Readers documents the process of reading development through stories of their early years. The author discusses the implications of natural reading development and its feasibility among preschoolers from different segments of the population. She also spells out, for parents and early childhood teachers, critical information on how preschool children should learn to read."--Jacket